Production Banana Glucose Syrup with the α-Amylase Supplementation - Ashifa Trisnaputri (International Journal of Applied Biology, 2018)
Indonesia is one of the largest producing country of banana in the world, but approximately only 1,5 million tons were consumed. As one of the fruit which contains the highest carbohydrate, the overripe banana with the high contains of sugar has a potential to be developed as the raw material of glucose syrup. According to the research, the banana with a lot of bruise or black mark on the skin has 2,6% strach, 33,6% reduction sugar, and 53,2% sucrose. In the making of banana glucose syrup, it will use α-amylase to hydrolize the strach. Based on the reduction sugar analysis there are nosignificantly different between the addition of 0,25 ml and 0,5 ml α-amylase. The results has qualified the minimum standard of glucose percentage (min. 30%) based on the reference SNI 01-2985-1992. The utilization of overripe bananas will greatly improve our glucose syrup production and ensure more of the banana waste can be saved in the future.